2021
DOI: 10.1021/acssensors.1c00674
|View full text |Cite
|
Sign up to set email alerts
|

Dual Methylation-Sensitive Restriction Endonucleases Coupling with an RPA-Assisted CRISPR/Cas13a System (DESCS) for Highly Sensitive Analysis of DNA Methylation and Its Application for Point-of-Care Detection

Abstract: High-performance detection of DNA methylation possesses great significance for the diagnosis and therapy of cancer. Herein, for the first time, we present a digestion strategy based on dual methylation-sensitive restriction endonucleases coupling with a recombinase polymerase amplification (RPA)-assisted CRISPR/Cas13a system (DESCS) for accurate and sensitive determination of site-specific DNA methylation. This dual methylation-sensitive restriction endonuclease system selectively digests the unmethylated targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…In the effort to avoid the reliance on fluorescence equipment and achieve better POCT feasibility, lateral flow assays are further combined with proposed CRISPR platforms for visual readout [23] , [24] , [25] . Albeit the significant progress in developing field-deployable lateral flow strips for SARS-CoV-2 detection, the readout capability is usually constrained to 1 gene per test, which severely impacts the accuracy and efficiency of the results [26] , [27] , [28] . During the diagnosis of COVID-19, multiplexed gene detection are recommended (for example, ORF1ab and N genes) to avoid the false negative or positive results caused by gene degradation or amplification errors [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…In the effort to avoid the reliance on fluorescence equipment and achieve better POCT feasibility, lateral flow assays are further combined with proposed CRISPR platforms for visual readout [23] , [24] , [25] . Albeit the significant progress in developing field-deployable lateral flow strips for SARS-CoV-2 detection, the readout capability is usually constrained to 1 gene per test, which severely impacts the accuracy and efficiency of the results [26] , [27] , [28] . During the diagnosis of COVID-19, multiplexed gene detection are recommended (for example, ORF1ab and N genes) to avoid the false negative or positive results caused by gene degradation or amplification errors [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…The integration of the CRISPR-Cas12a and nucleic acid amplification techniques has been proved by several works. 22,60,63–65 These results demonstrated that our nanopore sensor using a DNA tetrahedron as a signal transducer based on the CRISPR-Cas12a conversion mechanism could detect targets specifically, which we believe could become a promising alternative to biomolecular detection.…”
Section: Resultsmentioning
confidence: 74%
“…CRISPR-based biosensors also showed promising potential for the detection of non-infectious human diseases, such as cancer, based on the features with disease-related gene mutations, single-nucleotide polymorphism, DNA methylation, and so on ( Aman et al, 2020 ; Li B. et al, 2021 ; Wang et al, 2021c ; Chen Y. et al, 2021 ; Sheng et al, 2021 ). For example, a Cas12a-based biosensor showed sensitive detection of gene-PIK3CA H1047R mutation low at 0.001%, which has great potential to predict early-stage breast cancer ( Deng et al, 2021 ).…”
Section: Applications Of Crispr-based Biosensing Techniquesmentioning
confidence: 99%
“…Currently, clustered regularly interspaced short palindromic repeats (CRISPR) based biosensors have been developed as powerful tools for nucleic acid sensing and widely applied to the rapid diagnosis of infectious pathogens ( Kellner et al, 2019 ; Qin et al, 2019 ; Broughton et al, 2020 ; Ding R. et al, 2021 ; Song F. et al, 2021 ; Chen et al, 2021c ; Escalona-Noguero et al, 2021 ; Ge et al, 2021 ) and the detection of DNA or miRNAs associated with diseases such as cancer ( Li B. et al, 2021 ; Wang et al, 2021c ; Chen Y. et al, 2021 ). These biosensors rely on the CRISPR systems containing CRISPR-associated proteins (Cas) with nonspecific endonuclease activity to efficiently cleave specific targets via guide RNAs (gRNAs) ( Cong et al, 2013 ; Mali et al, 2013 ; van der Oost, 2013 ).…”
Section: Introductionmentioning
confidence: 99%